Applied machine learning - Gopal, M. (McGraw-Hill Education, 2019)
This comprehensive textbook explores the theoretical underpinnings of learning and equips readers with the knowledge needed to apply powerful machine learning techniques to solve challenging real-world problems. Applied Machine Learning shows, step by step, how to conceptualize problems, acurately represent data, select and tune algorithms, interpret and analyze results, and make informed strategic decisions. Presented in a non-rigorous mathematical syle, the book covers a broad array of machine learning ropics with special emphasis on methods that have been profitably employed.